2018
DOI: 10.1021/acsomega.8b02149
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization and Mineralization of Rhodamine B in Aqueous Solution with a Triple System of Cerium(IV)/H2O2/Hydroxylamine

Abstract: Hydroxylamine (HA) can react with hydrogen peroxide (H 2 O 2 ) to generate hydroxyl radical (HO • ), but the reaction rate between them is very slow (2.2 × 10 –4 M –1 s –1 ). We propose a new system to accelerate the formation of aminoxyl radical (NH 2 O • ) by the addition of cerium [Ce(IV)] to induce the continuous production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
2
16
1
Order By: Relevance
“…The UV-vis region of electromagnetic radiation, which corresponds to the bandgap, highlights the bandgap in the visible range. Earlier research found a similar pattern of behavior [42][43][44].…”
Section: Photocatalytic Activitysupporting
confidence: 58%
“…The UV-vis region of electromagnetic radiation, which corresponds to the bandgap, highlights the bandgap in the visible range. Earlier research found a similar pattern of behavior [42][43][44].…”
Section: Photocatalytic Activitysupporting
confidence: 58%
“…It was observed that the TOC removal efficiencies of RB, MO, NR, MB, and OII were 33.16%, 37.33%, 28.82%, 38.27%, and 32.74% respectively, after 20 min reaction. Although the results of this experiment were better than those of some similar reported degradation systems, 9,32,33 the low TOC removal efficiencies (o 40%) of different dye pollutants indicated that the mineralization rate of the OP/SS system should be increased in further research.…”
Section: Decolorization and Mineralization Of Different Dye Pollutantscontrasting
confidence: 63%
“…5c). This does not imply that limitless [H 2 O 2 ] 0 may be utilized; nevertheless, an optimal dose ([H 2 O 2 ] 0 , opt ¼ 1 mM) was found by Wang et al 45 for the degradation of Rhodamine B by the system Ce(IV)/H 2 O 2 /H 3 NOH + in which cerium(IV) performs the same catalytic function as Fe(II). Similarly, an optimum HSO 5…”
Section: Primary Oxidizing Speciesmentioning
confidence: 99%